(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
This study aims to find out how the role of the Social Service in improving the welfare of the Elderly (Elderly) displaced in Makassar City. The method used is a descriptive qualitative research technical analysis of the data used is collection, data reduction, data presentation, and data verification The results of this study indicate that the role of the social service in improving the welfare of neglected elderly is the role of the facilitative, the facilities provided are in the form of a handling house and Trauma Center (RPTC) for Persons with Social Welfare Problems (PMKS) as well as the needs of food clothing that is met. The role of education in the form of counseling about fostering in the form of mental guidance, social guidance to spiritual guidance that makes the elderly have more quality of life and has better welfare. The role of rerentational by inviting elderly is to do light gymnastics or elderly exercises which aims to physical fitness that can support the health and quality of life of the elderly becomes better.